Erratum: Measurement of the D*(2010)+ meson width and the D*(2010)+ - D0 mass difference - Lees, Jean-Pierre; Adametz, Aleksandra; Uwer, Ulrich (Physical review letters, 2013)
Phys. Rev. Lett. 111, 111801 (2013)
Im Titel ist das Pluszeichen "+", der Stern "*" und die Zahl "0" hochgestellt
The original article was published 9 September 2013
Gesehen am 16.11.2021